Does Socially Responsible Investing Pay in Developing Countries? A Comparative Study Across Select Developed and Developing Markets. Issue 2 (June 2022) - Tripathi, Vanita; Kaur, Amanpreet
Socially responsible investing (SRI) is the catalyst in aligning financial growth with sustainable development. The current study is an attempt to investigate the viability of responsible investment across major developing and developed countries of the world. The authors evaluate and compare the performance of socially responsible indices, against their general and conventional counterparts, in select developing and developed countries through market conditions of bull and bear over a 12-year window. Descriptive statistics and risk-adjusted-performance evaluation methods of performance evaluation reveal socially responsible investing to be non-penalizing in developing countries. Premium rewards earned by SRI help the responsibility indices in emerging countries secure topmost ranks, using Fama's decomposition model. While no significance in difference of performance is found among the indices in overall period, the study finds that the SRI strategy in emerging economies can provide investors with a safe investment vehicle during adversity. Thus, SRI can provide diversification benefit to the international investor seeking country effect, social impact as well as financial reward through responsible investing. The study on SRI index evaluation implies useful insights for achieving global sustainability goals through the use of financial tools to every market participant, especially in the era of globalization.